Pengaruh Seleksi, Pelatihan Terhadap Kompetensi Serta Dampaknya Pada Kinerja Karyawan - Dessi Setiyawan (JRB-Jurnal Riset Bisnis, 2018)
Background of this writing is whether there is influence of human resource competence in PT Sunthi Sepuri who have implemented ISO 9001: 2008 with the quality of employee performance. The organization's environment faces dramatic and spectacular changes. Environmental change is a challenge for businesses to reorganize business, structure, and direction of work. Increased growth is identical to the complexity of the work. Company in anticipating change, implementing strategy of orientation of MSDM and competence, training. For employees themselves require skill / skill adaptation / adaptation. The fact that happened to the company PT Sunthi Sepuri is competence and training is not as expected of the employees. Who has applied ISO 9001: 2008 In this research is to know the extent of competence and training applied by the company and how the effect on employee performance. So the purpose of this research is the influence after PT Sunthi Sepuri implement ISO 9001: 2008 on employee performance.